Pengembangan Titik Miquel Dalam Pada Sebarang Segilima - Zukrianto; Dinata, Okta; Soleh, Mohammad; Rahma, Ade Novia; Rahmawati (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2021)
The Miquel theorem is a theorem that applies to a triangle, namely the inner Miquel theorem and the outer Miquel theorem triangles—then developed on the quadrilateral. As of this writing, it is developed in any of the pentagons. Miquel’s theorem development in any pentagon is divided into two cases, namely in the convex and non-convex pentagons. This process begins with the construction of the inner Miquel point in any triangle using the GeoGebra application. While proving the internal Miquel theorem for any pentagon uses a simple concept, namely the concept of circles and cyclic rectangles so that five circles intersect at a point called the inner Miquel point at any pentagon.